GAMBARAN MEKANISME KOPING DAN BURNOUT PADA ORANG TUA SISWA SEKOLAH DASAR DI MASA PANDEMI COVID-19 - Sofiyantari, Ni Gusti Ayu Putu Intan; Devi, Ni Luh Putu Shinta; Nurhesti, Putu Oka Yuli (Coping: Community of Publishing in Nursing; Vol 11 No 2 (2023): April 2023DO - 10.24843/coping.2023.v11.i02.p01, 2023)
The change situation during the Covid-19 pandemic is a challenge for parents to raise their children. The role of parents during a pandemic can lead to burnout which causes emotional problems so there is a risk of violent behavior in children. Coping mechanisms are needed by parents to adapt difficult situations during a pressing pandemic. This study aimed to describe the coping mechanisms and burnout among parents of elementary school students during the Covid-19 pandemic. The design of this research was descriptive quantitative with a cross sectional approach. The sample size used were 261 parents of students from SDK ST. Maria Immaculata Tabanan and SD Negeri 1 Sembung Gede were selected used the proportional stratified random sampling. The results showed that the parents of elementary school students were in the late adult age category with a median value of 39 years old. Most of the parents in this study were female, college educated, married, had two child and were still working. The results of statistical tests showed that as many as 52,9% of parents used adaptive coping mechanisms and 47,1% of parents used maladaptive coping mechanisms. The results of the analysis of the burnout rate of parents are in the low category as much as 25,7%, the moderate burnout category as much as 49,4% and the high burnout category as much as 24,9%. It was concluded that most of the parents of elementary school students in this study used adaptive coping mechanisms and had moderate burnout levels during the Covid-19 pandemic.